Climate Change in the Arctic: Beyond the North Pole - Gómez de Ágreda, Ángel (Journal of the Spanish Institute for Strategic Studies, 2018)
Climate change is a global phenomenon the effects of which will be felt in different ways in every corner of the planet. Numerous papers and studies have described more or less the possible consequences of global warming at local level. However, changes which take place in such a specific environment as the Arctic will also reverberate well beyond the Polar Arctic Circle